Emphasize on overall banking activities & analyze the performance over last five years of Export Import Bank of Bangladesh Limited - Hoque, Sayda (BRAC University, 2011)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2010.